2022
DOI: 10.1186/s13019-022-01851-5
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcome of extensive mitral valve reconstruction with autologous pericardium and artificial chordae for treatment of destructive active infective endocarditis of the mitral valve

Abstract: Objective Mitral valve (MV) repair is a well-accepted surgical approach for infective endocarditis (IE). In our hospital, extensive MV reconstruction with fresh autologous pericardium (AP) and artificial chordae (AC) has been performed for patients with profoundly extensive and destructive IE in which valve reconstruction would be extremely challenging, especially in young patients to avoid mechanical valve replacement. Long-term outcome including the future performance of the newly created lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Valve repair using autologous tissues, such as the pericardium, is the most desirable procedure. Previous studies have reported the use of autologous pericardium to repair valves [ 3 , 4 ]. Although autologous tissue is a good option for compensating defective areas, its durability is a problem.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Valve repair using autologous tissues, such as the pericardium, is the most desirable procedure. Previous studies have reported the use of autologous pericardium to repair valves [ 3 , 4 ]. Although autologous tissue is a good option for compensating defective areas, its durability is a problem.…”
Section: Discussionmentioning
confidence: 99%
“…Surgeons usually have the following options: a fresh pericardium and a glutaraldehyde-treated pericardium. However, several controversies exist regarding shrinkage, calcification, and durability [ 3 , 5 ]. Shomura et al reported that the glutaraldehyde-treated autologous pericardium has good durability [ 8 ].…”
Section: Discussionmentioning
confidence: 99%